PREVENTIVE MAINTENANCE PADA COAL PREVENTIVE MAINTENANCE PADA COAL MILL (PULVERIZER) - ISMAEL , ALIF RAHMAN PELDIANSYAH; Witanto, Yovan; Helmizar (UNIB Press, 2025)
Coal mill (pulverizer) is used to grind coal into micro-sized particles suitable for combustion. This study aims to analyze the preventive maintenance applied to the coal pulverizer to prevent damage and improve operational efficiency. Preventive maintenance procedures include routine tasks such as visual inspection, lubrication, cleaning, and component tightening. During the process, problems such as hydraulic pipe leakage and other component malfunctions are identified and immediately addressed to prevent further impacts. Preventive maintenance has proven effective in minimizing the risk of unplanned downtime, supporting sustainable production, and improving the efficiency of the coal pulverizer. The operational principle of the pulverizer involves grinding coal between the grinding roller and the grinding table, assisted by airflow from the primary air fan to produce coal powder with a size of 200 mesh, ready for combustion in the burner. In conclusion, preventive maintenance is very important to maintain equipment performance, reduce potential damage, and ensure smooth production processes.